Chemotherapy for resected colorectal cancer pulmonary metastases: Utilization and outcomes in routine clinical practice. Issue 8 (August 2017) - Karim, S.; Nanji, S.; Brennan, K.; Pramesh, C.S.; Booth, C.M.
Abstract: Background: The role of chemotherapy in the setting of resected colorectal cancer pulmonary metastases (CRCPM) is not well defined. Here we describe utilization of peri-operative chemotherapy and outcomes among patients with resected CRCPM in the general population. Methods: All cases of CRCPM who underwent resection from 2002 to 2009 were identified using the Ontario Cancer Registry (OCR). Electronic treatment records identified peri-operative chemotherapy delivered within 16 weeks before or after pulmonary metastasectomy (PM). Modified Poisson regression was used to evaluate factors associated with chemotherapy delivery. Cox proportional models were used to explore the association between post-operative chemotherapy and cancer-specific (CSS) and overall survival (OS). Results: The study population included 420 patients. Thirty-six percent of patients (151/420) received peri-operative chemotherapy. Among these patients, 75% (113/151) received post-operative chemotherapy. Factors that were independently associated with use of post-operative chemotherapy included higher socioeconomic status (SES) and no prior adjuvant chemotherapy (p < 0.01). In adjusted analyses post-operative chemotherapy was not associated with improved CSS (HR 0.99, 95% CI 0.67–1.47) or OS (HR 0.93 95% CI 0.66–1.31). In exploratory analyses, among those patients who did not receive previous adjuvant therapy for the primary colorectal cancer, post-operative chemotherapy following lung metastasectomy was associated with HR 0.50 (95% CI 0.27–0.95) for OS and HR 0.59 (95% CI 0.27–1.27) for CSS. Conclusion: One third of patients with resected CRCPM in routine practice receive peri-operative chemotherapy. A randomized controlled trial is warranted to evaluate whether chemotherapy following resection of CRCPM is associated with improved survival.